Towards prosocial design: a scoping review of the use of robots and virtual agents to trigger prosocial behaviour - Oliveira, R.; Arriaga, P.; Santos, F. P.; Mascarenhas, S.; Paiva, A. (Computers in Human Behavior, 2021)
Context: Increased attention has been placed on the role of technological artefacts in the promotion of prosocial behaviours. However, up to this date, there is still no systematic exploration of the effectiveness of robots and virtual agents as promoters of this type of behaviour. Goals: The goal of this paper is to map research on the effectiveness of interventions involving interaction with social robots and virtual agents in eliciting prosocial behaviours in humans, as well as to derive implications for future research and development of these agents. Method: We identified 272 publications relevant to our goals, retrieved from 7 pertinent digital libraries in the areas of Human–Computer Interaction and Psychology. The final sample of primary sources included 19 publications (reporting on the results of 23 independent studies) involving at least 1524 subjects. The sources included were peer-reviewed research articles involving direct contact with robots or virtual agents, published in English between January 1st of 2000 and May 31st of 2020. Results: Of the 23 studies included, 22% did not find evidence to support an association between interaction with social robots or virtual agents and engagement or intention to engage in prosocial behaviours; and 26% reported mixed results. The remaining 52% of the studies reported positive effects in prosociality resulting from interaction with robots or virtual agents. The majority of these studies included interaction with robots (n=20) and was aimed at invoking prosocial behaviours towards the socially interactive agent itself. Most studies presented a satisfactory level of quality. Conclusions: There is a potential promise for social robots and virtual agents to serve as elicitors of prosocial behaviour among humans, both directed at the wider community and at the robot or agent itself. Nonetheless, further research is warranted to clarify the design and interaction-related variables that can increase the level of effectiveness of these technological agents, specially in what concerns virtual agents.